Spin–Phonon Coupling in Ferromagnetic Monolayer Chromium Tribromide. Issue 20 (14th April 2022) - Wu, Jiangbin; Yao, Yu; Lin, Miao‐Ling; Rösner, Malte; Du, Zhonghao; Watanabe, Kenji; Taniguchi, Takashi; Tan, Ping‐Heng; Haas, Stephan; Wang, Han
Abstract: Novel 2D magnets exhibit intrinsic electrically tunable magnetism down to the monolayer limit, which has significant value for nonvolatile memory and emerging computing device applications. In these compounds, spin–phonon coupling (SPC) typically plays a crucial role in magnetic fluctuations, magnon dissipation, and ultimately establishing long‐range ferromagnetic order. However, a systematic understanding of SPC in 2D magnets that combines theory and experiment is still lacking. In this work, monolayer chromium tribromide is studied to investigate SPC in 2D magnets via Raman spectroscopy and first principle calculations. The experimental Curie temperature and phonon shifts are found to be in good agreement with the numerical simulations. Specifically, it is demonstrated how magnetic exchange interactions affect phonon vibrations, which helps establish design fundamentals for 2D magnetic materials and other related devices. Abstract : Spin–phonon coupling in monolayer chromium tribromide is investigated via Raman spectroscopy in combination with first principle calculations. The experimental Curie temperature and phonon shifts are in good agreement with numerical simulations. This work demonstrates how magnetic exchange interactions affect the phonon vibrations and establishes the missing guidelines for the design of the 2D magnetic materials and related devices.